Indigenous Development in the Andes : Culture, Power, and Transnationalism - Andolina, Robert, 1968- (Book collections on Project MUSE., 2009)
Analyzes the transnational relations of indigenous politics after their shift to the global level, and explores how the contest between neo-liberal economics and anti-free market politics generates new forms of development and culture.